Institutions and Incentives in Antitrust Enforcement - Spencer Weber Waller (Market and Competition Law Review)
The United States Supreme Court has decided in a number of cases how Section One 1 of the Sherman Act should apply to agreements that potentially harm competition. In recent key cases, the Court stated that the rule of reason is the default rule in antitrust. Second, per se condemnation (or some rebuttable presumption) is reserved for a limited group of practices that economics and experience show that the type of agreement under consideration is inevitably destructive of competition with little or no redeeming features. Third, reasonable people can disagree about the likely competitive effects of a particular type of agreement. Therefore, lower courts going forward should apply the rule of reason on a case by case basis to determine whether there is any likelihood of competitive harm and any likelihood of significant procompetitive benefits. However, lower courts should structure and streamline their analysis by applying one or more rules of thumb.  The Supreme Court followed this basic approach in Leegin, applying the rule of reason to resale price maintenance agreements (vertical price fixing), and in Actavis, applying the rule of reason to pay-for-delay agreements involving branded and generic pharmaceutical manufacturers. This essay explores where this strategy has been successful (Actavis) and where it has not (Leegin). I focus not on the substantive law but instead on the institutions and incentives in antitrust enforcement that ensure that the pronouncements of the law on the books by the Supreme Court get translated into the law in action in the lower courts and the real world.